Biochemical evaluation of linseed (Linum usitatissimum) for oil and cake - VAJPEYI, MADHU; ABHISHEK, ABHISHEK; SHUKLA, SHARWAN KUMAR; SRIVASTAVA, R L (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2005, at CSA University Agriculture & Technology, Kanpur to evaluate 40 linseed (Linum usitatissimum L.) varieties for physical and biochemical constituents of seed, namely 1 000 seed weight, moisture content, oil content and oil quality parameters, viz iodine value and fatty acid profile, protein content, amino acid (tryptophan) content and polyphenol content. A significant variability was observed in almost all the quality characters. Among the genotypes, highest 1 000 seed weight was recorded by ‘Laxmi 27’, highest moisture content by ‘Shubhra’, highest oil content in ‘K 2’. ‘Neela’ and ‘Pusa 3’ contained highest protein and tryptophan contents respectively. The ‘LC 185’ showed highest values for linolenic acid and iodine number. As regards antinutritional constituent ‘J 23’ showed highest (3.93%) while Kiran recorded lowest (2.25%) polyphenol content.